Insider trading patterns - Biggerstaff, Lee; Cicero, David; Wintoki, M. Babajide (Journal of Corporate Finance, 2020)
We revisit the information content of stock trading by corporate insiders with an expectation that opportunistic insiders will spread their trades over longer periods of time when they have a longer-lived informational advantage, and trade in a short window of time when their advantage is fleeting. Controlling for the duration of insiders' trading strategies, we find robust new evidence that both insiders' sales and purchases predict abnormal stock returns. In addition, we provide evidence that insiders attempt to preserve their informational advantages and increase their trading profits by disclosing their trades after the market has closed. When insiders report their trades after business hours, they are more likely to engage in longer series of trades, they trade more shares overall, and their trades are associated with larger abnormal returns. Finally, we show how accounting for these trading patterns sharpens screens for corporate insiders who trade on infor- mation.